Utilization Of Cockle Shells As Partial Binder Replacement In Concrete - Nor Hisham, N. F.; Razali, N.; Razali, N. (Journal of Engineering and Technology (JET), 2017)
The main aim of this study is to investigate the performance of calcined cockle shell as partial binder replacement in modified concrete (MC). Cockle shell was selected based on its high calcium carbonate (CaCO3) content; an active ingredient in cement manufacturing. The investigation was carried out by substituting the cement in the conventional concrete formulation with percentages of calcined cockle shells powder (10%, 20%, 30% and 40% respectively). Primary concrete parameters such as pH, carbonation depth, compressive strength and sorptivity were studied for the periods of 56 days. The results showed that modified concretes exhibit superior performance than the control specimens, which is strongly influenced by the amount of substitution. The addition of calcium carbonate in the mixture is proven to increase the physical performance especially carbonation depth. However, the modified concretes’ strength developments are inversely proportional to the amount of substitution. It is believed that the aragonite polymorphs contribute to the low strength development due to its different symmetry and crystal shapes to calcite, thus leading to poor bonding properties of the matrix with aggregates. No significant strength developments are observed after 28 days for all modifications.